1988
DOI: 10.1145/42186.42323
|View full text |Cite
|
Sign up to set email alerts
|

A relational approach to monitoring complex systems

Abstract: Monitoringis an essential part of many program development tools, and plays a central role in debugging, optimization, status reporting, and reconfiguration. Traditional monitoring techniques are inadequate when monitoring complex systems such as multiprocessors or distributed systems. A new approach is described in which a historical database forms the conceptual basis for the information processed by the monitor. This approach permits advances in specifying the low-level data collection, specifying the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(55 citation statements)
references
References 38 publications
1
52
0
2
Order By: Relevance
“…Snodgrass has shown that a relational database query language can be used beneficially to specify queries that are evaluated against event streams such as are generated with on-line monitoring [23]. The significant difference between evaluating queries against a database and evaluating them against an event stream is that in the latter constraints must be evaluated against a conceptual database rather than an actual database.…”
Section: Applying a Query Language To On-line Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Snodgrass has shown that a relational database query language can be used beneficially to specify queries that are evaluated against event streams such as are generated with on-line monitoring [23]. The significant difference between evaluating queries against a database and evaluating them against an event stream is that in the latter constraints must be evaluated against a conceptual database rather than an actual database.…”
Section: Applying a Query Language To On-line Monitoringmentioning
confidence: 99%
“…It has been shown that the relational model is an appropriate formalism for the information processed by the monitor though earlier applications of this formalism to monitoring were primarily for performance evaluation [9,23]. In addition, prior approaches to monitoring were static, that is, they required that all constraints be known at compile time.…”
Section: Synchronous Constraint Checkingmentioning
confidence: 99%
“…Events may be extracted from files, received from sockets, or received as signals from an electro-mechanical sensor. When modeled in the context of our relational approach, an event is described as a database tuple [13]. All events of a given type are then members of the same relation, and relation membership is distinct (i.e., no tuple belongs to more than one relation.…”
Section: Approachmentioning
confidence: 99%
“…Although similar to ours in its support of temporal and complex specifications, this work cannot be directly applied to run-time detection. Snodgrass [13] develops an information based approach to modeling program behavior that treats monitoring information (runtime data, states of processes, states of processors, messages, etc.) as relations.…”
Section: Related Workmentioning
confidence: 99%
“…A false negative is a match that should have been made that is missed [9]. A reasonable window size depends strongly on the temporal ordering of the two input streams used in the join and on their relative synchrony [14]. For two event streams, each with a guaranteed partial order and containing an event for every logical timestep, minimal storage would be required.…”
Section: Query Language Through Examplesmentioning
confidence: 99%